Analisis Kesalahan Mahasiswa Pada Soal Pohon Rentang Minimum Menggunakan Algoritma Prim dan Kruskal Menurut Teori Newman - Finanta Diva Sabila; Ahmad Rizki; Meli Lestari; Fransiska Anita; Ahmad Yani T; Nadya Febriani Meldi (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to examine the mistakes made by students when solving the minimum range tree problem using the Prim and Kruskal algorithms. This study applies a qualitative descriptive approach, involving 23 students in the fifth semester of the Mathematics Education Study Program, Tanjungpura University Pontianak as research subjects. Data was collected using test, interview, and documentation methods. Data analysis techniques involve stages in the form of data reduction, data presentation, and conclusion drawn.  Furthermore, the data was analyzed based on Newman's theory, which included reading errors, comprehension errors, transformation errors, process skills errors, and answer writing errors. The results of the study revealed that students tended to make reading mistakes most often with a total of 9 errors (47.36%), process skills errors with a total of 4 errors (21.05%), and answer writing errors with a total of 6 errors (31.58%). No misunderstandings and transformations were found. The main causes of errors are lack of focus, inadequate understanding of the concept of prim and crucial algorithms, and lack of precision in working on problems. This research recommends the need for a deeper understanding of the concept of primordial and crucial algorithms, as well as an increase in students' accuracy in reading and rechecking answers.